Recent Progress in Robotics: Viable Robotic Service to Human An Edition of the Selected Papers from the 13th International Conference on Advanced Robotics - Lee, Sukhan; Suh, Il Hong.; Kim, Mun Sang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
th This volume is an edition of the papers selected from the 13 International Conference on Advanced Robotics, ICAR 2007, held in Jeju, Korea, August 22-25, 2007, with the theme: (3z(BViable Robotics Service to Human. (3y (BIt is intended to deliver readers the most recent technical progress in robotics, in particular, toward the advancement of robotic service to human. To ensure its quality, this volume took only 28 papers out of the 214 papers accepted for publication for ICAR 2007. The selection was based mainly on the technical merit, but also took into consideration whether the subject represents a theme of current interest. For the final inclusion, authors of the selected papers were requested for another round of revision and expansion. In this volume, we organize the 28 contributions into three chapters. Chapter 1 covers Novel Mechanisms, Chapter 2 deals with perception guided navigation and manipulation, and Chapter 3 addresses human-robot interaction and intelligence. Chapters 1, 2 and 3 consist of 7, 13 and 8 contributions, respectively. For the sake of clarity, Chapter 2 is divided further into two parts with Part 1 for Perception Guided Navigation and Part 2 for Perception Guided Manipulation. Chapter 3 is also divided into two parts with Part 1 for Human- Robot Interaction and Part 2 for Intelligence. For the convenience of readers, a ch- ter summary is introduced as an overview in the beginning of each chapter. The chapter summaries were prepared by Dr. Munsang Kim for Chapter 1, Prof.s
I: Novel Mechanisms -- Summary of Novel Mechanisms -- Feasibility Study of Robust Neural Network Motion Tracking Control of Piezoelectric Actuation Systems for Micro/Nano Manipulation -- Hybrid Formation Control for Non-Holonomic Wheeled Mobile Robots -- Novel Tripedal Mobile Robot and Considerations for Gait Planning Strategies Based on Kinematics -- Safe Joint Mechanism Based on Passive Compliance for Collision Safety -- A Guidance Control Strategy for Semi-autonomous Colonoscopy Using a Continuum Robot -- Fully-Isotropic T1R3-Type Redundantly-Actuated Parallel Manipulators -- Early Reactive Grasping with Second Order 3D Feature Relations -- II: Perception Guided Navigation and Manipulation -- Summary of Perception Guided Navigation and Manipulation -- Link Graph and Feature Chain Based Robust Online SLAM for Fully Autonomous Mobile Robot Navigation System Using Sonar Sensors -- Services Robots Navigating on Smart Floors -- Control of Many Agents by Moving Their Targets: Maintaining Separation -- Improved Mapping and Image Segmentation by Using Semantic Information to Link Aerial Images and Ground-Level Information -- Active Visual Search by a Humanoid Robot -- Visual Control of a Micro Helicopter under Dynamic Occlusions -- Visual Servoing from Spheres with Paracatadioptric Cameras -- Dynamic Targets Detection for Robotic Applications Using Panoramic Vision System -- Vision-Based Control of the RoboTenis System -- Particle Filter Based Robust Recognition and Pose Estimation of 3D Objects in a Sequence of Images -- Preliminary Development of a Line Feature-Based Object Recognition System for Textureless Indoor Objects -- Modelling of Second Order Polynomial Surface Contacts for Programming by Human Demonstration -- Robot Self-modeling of Rotational Symmetric 3D Objects Based on Generic Description of Object Categories -- III: Human-Robot Interaction and Intelligence -- Summary of Human-Robot Interaction and Intelligence -- Dynamic Speech Interaction for Robotic Agents -- Hand Posture Recognition Using Adaboost with SIFT for Human Robot Interaction -- Multimodal Navigation with a Vibrotactile Display in Computer Assisted Surgery -- Two Arms Are Better Than One: A Behavior Based Control System for Assistive Bimanual Manipulation -- A Customizable, Multi-host Simulation and Visualization Framework for Robot Applications -- Imitation of Walking Paths with a Low-Cost Humanoid Robot -- Intelligent Robot Software Architecture -- Ontology-Based Semantic Context Modeling for Object Recognition of Intelligent Mobile Robots.
Keywords: Engineering; System theory; Control engineering; Robotics; Mechatronics; Automation; Engineering; Robotics and Automation; Control, Robotics, Mechatronics; Systems Theory, Control; Electronic books